Encyclopedia of Inorganic and Bioinorganic Chemistry 2015
DOI: 10.1002/9781119951438.eibc2329
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Iron Cluster‐Containing OxygenaseCmlA

Abstract: CmlA is a tailoring enzyme from the nonribosomal peptide synthetase (NRPS)‐based biosynthetic pathway for chloramphenicol expressed in Streptomyces venezuelae . The enzyme is a monooxygenase that catalyzes the β‐hydroxylation of l ‐ para ‐aminophenylalanine ( l ‐PAPA) covalently tethered to the NRPS CmlP. Spectroscopic and X‐ray crystallographic studies reveal an oxo‐bridged dinuclear iron cluster in the active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The X-ray crystal structure of CmlA was subsequently solved at 2.17 Å resolution using phasing from a selenomethionine-substituted protein. 14, 16 In accord with the sequence predictions, the enzyme was found to fold into two domains as shown in Figure 2A with a short linker region (residues 236-248) that connects these two domains. The N-terminal (residues 1-235) domain has no structural homologs.…”
Section: Cmla – the β-Hydroxylase In Nrps-linked Chloramphenicol Bisupporting
confidence: 68%
See 3 more Smart Citations
“…The X-ray crystal structure of CmlA was subsequently solved at 2.17 Å resolution using phasing from a selenomethionine-substituted protein. 14, 16 In accord with the sequence predictions, the enzyme was found to fold into two domains as shown in Figure 2A with a short linker region (residues 236-248) that connects these two domains. The N-terminal (residues 1-235) domain has no structural homologs.…”
Section: Cmla – the β-Hydroxylase In Nrps-linked Chloramphenicol Bisupporting
confidence: 68%
“…As illustrated in Figure 4C, computational docking studies suggested that the binding orientation of L-PAPA in the active site would place the β-carbon immediately over the newly opened coordination site on Fe1 where O 2 would bind and be activated. 14, 16 This placement would also allow a hydrogen bond to form between one of the carboxylate oxygens of E377 and the amine of L-PAPA if E377 would rotate into a monodentate binding orientation. Thus, substrate binding both initiates O 2 activation and fixes the substrate in the correct orientation to be hydroxylated.…”
Section: Cmla – the β-Hydroxylase In Nrps-linked Chloramphenicol Bimentioning
confidence: 99%
See 2 more Smart Citations
“…2, 3 Structurally similar clusters are found in many enzymes that activate O 2 and then catalyze reactions such as functionalization of unactivated C-H bonds, desaturation reactions, aromatic hydroxylation, and radical formation, but notably, not aryl-amine oxygenation. 4-14 Conversely, CmlI and its structural and function homolog AurF 15-19 do not catalyze the types of reactions common to other diiron oxygenases. Kinetic and spectroscopic studies of CmlI and AurF have shown that, despite the structural similarities to other diiron oxygenases, a different type of reactive oxygen intermediate is generated during catalysis.…”
Section: Introductionmentioning
confidence: 99%